RANGKA KERJA PERANCANGAN MODEL MASKOT UNTUK SEKOLAH ALAM DEPOK - Hedi Amelia Bella Cintya; Hairunnas Hairunnas; Tania Kurniawan; Mohamad Zaki Afandi (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
The visual identity of a school can be used as a promotional medium. With a significant number of primary schools in Indonesia, competition among schools has become intense. Educational institutions require innovative approaches to promote themselves. One popular promotional method is the use of mascot characters. Creating appealing characters is an effective way to ensure easy recall. However, the design of these characters should not only be aesthetically pleasing but also convey the visual identity and message of the institution. Several criteria need to be met, necessitating a guideline on how a mascot can comprehensively represent the identity and message of a school. The purpose of the conducted research is to address this issue. The research adopts the Design Research Methodology (DRM) model to accomplish its objectives. The study produces a framework that can be utilized to create a mascot that represents the visual aspects of an educational institution. In addition to developing the framework for mascot creation, the research also conducts an evaluation of the established framework. The evaluation consists of two important criteria tested separately, involving multiple parties. The first evaluation aims to assess the understanding of the framework and the appropriateness of the characters designed using the framework. The results of the evaluation demonstrate that the created framework successfully addresses the formulated problem. Keywords: Character Design, Framework, Mascots, School’s Identity